Mobility and Modernity in Women's Novels, 1850s-1930s - Parkins, W. author. aut Link
VI, 198 p.
Keywords: Analyzing novels by women writers from the 1850s to the 1930s, this book argues that representations of mobility offer a fruitful way to explore the location of women within modernity and, specifically, the opportunities for (or limitations on) women's agency in this period, considering the mobility of the female subject in the city and beyond.